Knowledge Transfer Experiences of Inpatriates in Multinational Companies - A Cognitive Dissonance Perspective - Schuster, Tassilo; Bernhard, Theresa; Jack, A. (Expatriates: Perspectives and Challenges of the 21st Century, 2019)
Inpatriates have become important means of knowledge transfer within multinational companies. Delegating foreign managers to the domestic management team enables MNCs to secure their long-term survival. But how can these employees be motivated to share their knowledge? In this exploratory study, we attempt to extract more information about knowledge transfer processes and inpatriates’ behavioral patterns. To provide a rich understanding of these processes from the inpatriates’ perspective, critical incidents reported by 22 inpatriates were content-analyzed. Using cognitive dissonance theory as theoretical framework, this study provides new insights about behavioral processes of inpatriates during their knowledge transfer experiences. The interview analysis reveals, for example, that inpatriates frequently exhibit dysfunctional behavior when they experience cognitive dissonance. Based on the results from this analysis, we deduce meaningful practical and theoretical implications for human resource departments and highlight directions for future research.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Cognitive dissonance theory; Conceptual study/qualitative study/exploratory study; Grounded theory approach; Inpatriate management; Inpatriates; Inpatriation; International assignments; Reputational asymmetry

Peer performance evaluations in global virtual teams: A longitudinal analysis of surface- and deep-level attributes - Tavoletti, Ernesto; Bernhard, Theresa; Dong, Longzhu; Taras, Vas (Journal of International Management, 2023)
Most research on peer performance evaluations (PPEs) has been conducted using co-located teams, assuming that PPEs are static, and focusing on the effects of PPEs, while ignoring how attributes of the evaluated individual influence PPEs, and if PPEs may vary over time. The present study advances this line of research by applying theory on impression formation and Tuckman's team stages model to explore the varying relevance of surface-level and deep-level individual attributes on PPEs across the team's life, and specifically in the context of global virtual teams (GVTs). We used longitudinal data across ten weeks of 831 individuals from 34 countries working in 239 different GVTs. We found that surface-level attributes, such as age and home country reputation, affect PPEs in the early stages of the team project, while the deep-level attributes, such as cognitive ability and English language proficiency, influence PPEs in the late phase of a GVT's life. We also found that cultural intelligence impacts PPEs relatively early on, and emotional intelligence is only relevant for PPEs when the GVT hits critical turning points, while gender influences PPEs throughout the project. We discuss the theoretical and managerial implications of our findings and provide directions for future research on PPEs in GVTs.
CRIS-Team Scopus Importer:2023-03-31
Keywords: Categorization; Deep-level attributes; Global virtual teams; Peer evaluations; Peer performance evaluations; Surface-level attributes; X-culture; Kulturelle Vielfalt

The use and usefulness of artificial intelligence in international business education. Evidence from a field study - Holtbrügge, Dirk; Wicht, Luisa; Bernhard, Theresa (International Journal of Management Education, 2025)
This field study is among the first empirical investigations into the integration of an artificial intelligence (AI) enhanced video course in management and international business (IB) education. Moving beyond conceptual discussions, it evaluates the use and perceived usefulness of an AI-enhanced video course in a real classroom setting. Findings highlight that such AI tools support personalized learning, increase student engagement, and offer particular benefits for culturally diverse learners by reducing communication barriers and accommodating different educational backgrounds. While exploratory in scope, the study offers practical insights for educators seeking to implement AI in an inclusive and effective manner. Limitations include reliance on self-reported perceptions and a focus solely on student experiences. Future research should examine the impact of AI on learning outcomes and explore the reasons for using AI tools further, for example by investigating emotional and affective components.
CRIS-Team Scopus Importer:2025-09-12
Keywords: Artificial intelligence; Educational videos; Field study; International business education; Personalized learning; Usage; User satisfaction

When the Chinese guy becomes the female IT specialist Liu – a conceptualization of reputational shifts in international assignments - Bernhard, Theresa; Holtbrügge, Dirk (Journal of Global Mobility, 2021)
Purpose: International assignments rely on interactions between host country nationals (HCNs) and an international assignee (IA). These interactions are significantly determined by the reputation that the IA holds among HCNs. However, reputation has only scarcely been addressed in extant mobility research, and there is a lack of understanding about how the reputation of an IA shifts among HCNs during the course of an assignment. The purpose of this paper is to understand the development of an individual's reputation as well as the interactions between an IA and HCNs in the context of international assignments. Design/methodology/approach: This is a conceptual paper that builds upon the central idea in extant research of individual reputation as a social construction and draws on sensemaking theory to develop its conceptual model. Findings: As extant research argues for both a temporal and dynamic dimension of reputation, the authors introduce time and reputational richness as central model elements. Furthermore, the conceptual model proposes reputational events as the principal triggers for reputational shifts. Reputational events reveal quantitatively and qualitatively new informational cues about the IA to HCNs, who then use these cues to incrementally construct the IA's reputation in sensemaking processes. In addition, contextual factors of reputational shifts, namely accelerators and amplifiers, are discussed. The authors argue that these contextual factors may affect both the timing and the strength of reputational shifts. Originality/value: The study introduces a novel conceptual model and contributes to the understanding of individual reputation development as well as the interactions between an IA and HCNs in international assignments.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Conceptual study; Host country nationals; International assignments; Reputational shifts; Sensemaking; Social construction; Kulturelle Vielfalt